Impacts of Storm “Zyprian” on Middle and Upper Atmosphere Observed from Central European Stations - Petra Koucká Knížová; Kateřina Potužníková; Kateřina Podolská; Tereza Šindelářová; Tamás Bozóki; Martin Setvák; Marcell Pásztor; Csilla Szárnya; Zbyšek Mošna; Daniel Kouba; Jaroslav Chum; Petr Zacharov; et al. (Remote Sensing)
Mesoscale convective systems are effective sources of atmospheric disturbances that can reach ionospheric heights and significantly alter atmospheric and ionospheric conditions. Convective systems can affect the Earth’s atmosphere on a continental scale and up to F-layer heights. Extratropical cyclone “Zyprian” occurred at the beginning of July, 2021 and dominated weather over the whole of Europe. An extensive cold front associated with “Zyprian” moved from the western part to the eastern part of Europe, followed by ground-level convergence and the formation of organized convective thunderstorm systems. Torrential rains in the Czech Republic have caused a great deal of damage and casualties. Storm-related signatures were developed in ground microbarograph measurements of infrasound and gravity waves. Within the stratosphere, a shift of the polar jet stream and increase in specific humidity related to the storm system were observed. At the ionospheric heights, irregular stratification and radio wave reflection plane undulation were observed. An increase in wave-like activity was detected based on ionograms and narrowband very-low-frequency (VLF) data. On directograms and SKYmaps (both products of digisonde measurements), strong and rapid changes in the horizontal plasma motion were recorded. However, no prevailing plasma motion direction was identified within the F-layer. Increased variability within the ionosphere is attributed mainly to the “Zyprian” cyclone as it developed during low geomagnetic activity and stable solar forcing.